Analisis Pemilihan Moda Transportasi Angkutan Umum Di Kota Kendari - Maisara, Maisara; Hakiman, Hakiman; hujiyanto, hujiyanto; Munandar, Fikri Aris (Sultra Civil Engineering Journal (SCiEJ), 2023)
This study aims to determine the characteristics of travelers who use modes of transportation and find out how big the probability by choosing one of transportation mode is in Kendari City. The result show that the characteristics of mode selection based on the reasons that influenced the choice of mode from a total of 73 respondents were as follows, the travelers chose faster time considerations by 48% or as many as 35 people, the travelers who chose security considerations by 11% or as many as 8 people, the travelers who chose convenience considerations by 19% or as many as 14 people, and travelers who chose price considerations by 22% or as many as 22 people. The probability of users of transportation modes in Kendari City shows that people are more likely to use online modes of transportation 51% compared to using public transportation modes of 49%